2021
DOI: 10.1002/mp.14670
|View full text |Cite
|
Sign up to set email alerts
|

A tool for patient‐specific prediction of delivery discrepancies in machine parameters using trajectory log files

Abstract: Purpose Multileaf collimator (MLC) delivery discrepancy between planned and actual (delivered) positions have detrimental effect on the accuracy of dose distributions for both IMRT and VMAT. In this study, we evaluated the consistency of MLC delivery discrepancies over the course of treatment and over time to verify that a predictive machine learning model would be applicable throughout the course of treatment. Next, the MLC and gantry positions recorded in prior trajectory log files were analyzed to build a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 33 publications
0
56
0
1
Order By: Relevance
“…treatment site) can be used as model input features. Various ML and DL models were trained to map the plan complexity features alone or with other dosimetric features 33–35,38,41,43–48,51 . Complexity metrics can be related to the QA outcome results, offering a troubleshooting method in case a plan fails the QA.…”
Section: Applications Of Ml/dl For Patient‐specific Imrt/vmat Qamentioning
confidence: 99%
See 3 more Smart Citations
“…treatment site) can be used as model input features. Various ML and DL models were trained to map the plan complexity features alone or with other dosimetric features 33–35,38,41,43–48,51 . Complexity metrics can be related to the QA outcome results, offering a troubleshooting method in case a plan fails the QA.…”
Section: Applications Of Ml/dl For Patient‐specific Imrt/vmat Qamentioning
confidence: 99%
“…Their model revealed high prediction accuracy for all individual MLCs with a maximum root MSE (RMSE) of 0.0097 mm between the predicted and the actual leaf positions. Chuang et al 43 studied various regression ML models including simple and multivariate linear regressions, decision tree, and ensemble method (boosted tree and bagged tree model) using trajectory log files data to predict thee MLC positional errors for IMRT and VMAT treatment. The results showed that the boosted tree model had the best performance with RMSE of 0.0085 mm.…”
Section: Applications Of ML / Dl For Patient‐specific Imrt / Vmat Qamentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, uncertainties in dose calculation can now be quantified directly via Monte Carlo (MC)‐based independent calculation 13 . Uncertainties in machine parameters at delivery are quantifiable via trajectory files, and, if desired, performance for individual plans can be accurately predicted using AI 14,15 . This approach has major advantages: (a) it solves the clinical relevance problem since results can be used to directly and unambiguously calculate effect on patient dose‐volume histogram (DVH), and (b) it decouples clinically irrelevant uncertainties related to the PSQA process.…”
Section: Against the Proposition: Justus Adamson Phdmentioning
confidence: 99%